Working and Caring: The Simultaneous Decision of Labor Force Participation and Informal Elderly and Child Support Activities in Mexico (2015)
We analyze factors determining women’s decisions to participate in the labor market and provide elderly care and nonfinancial support to their (grand)children. We use data from the Mexican Health and Aging Study, a survey of people aged 50 and over, applying a three-equation, reducedform SUR model. Results suggest that care needs are the driving force behind caregiving activities. Traditional roles also appear to be relevant in the labor force participation decision: women with a closer labor market connection when they were young are more likely to work. Simulations of demographic changes illustrate potential ef fects for future caregiving and participation rates.